USEFUL PROPERTIES OF WHITE AND BLACK (SESAME) SESAME PLANTS AND AGROTECHNICS OF CULTIVATION (Scientific journal of the Fergana State University, 2025)
Sesame (Sesamum) is an annual and perennial plant belonging to the Sesamaceae family family of plants, oilseed. 19 types are known. Homeland - Africa. to Central Asia Imported from India. Indian sesame (S. indicum L.), a one-year cultivated type that is a spring crop in agriculture, is cultivated in India, China, South-East Asia, Africa, Iran, Central Asia and other countries.